Penerapan Metode Proyek untuk Meningkatkan Keterampilan Proses IPAS Sekolah Dasar kelas V pada Kurikulum Merdeka: Penerapan Metode Proyek untuk Meningkatkan Keterampilan Proses IPAS Sekolah Dasar - Rahma, Sri Rahmawati; Nanda Faradita, Meirza; Ayu Afiani, Kunti Dian Ayu Afiani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This research aimed to describe the implementation of the project method and improve the science and social (IPAS) process skills for grade V elementary school in the merdeka curriculum using the project method. The subjects of this research were class V (centaurus) students at SD Muhammadiyah 18 Surabaya with a total of 28 students, consisting of 16 male students and 12 female students. This type of research used Classroom Action Research with 2 cycles. Data collection techniques were carried out using observation sheets. The results of applying the project method to students’ IPAS process skills in cycle I were less conducive and less enthusiastic in working on their group’s IPAS ass clipping because the tools and materials were incomplete. Meanwhile, in cycle II, the application of the project method to students’ IPAS process skills was very conducive and enthusiastic in working on their group’s IPAS ass clipping because the project tools and materials were complete. Data from observations of science process skills in cycle I showed that there were four groups of indicator achievement percentages of 80% with sufficient criteria, one group of indicator achievement percentages of 20% with insufficient criteria and in cycle II there was an increase in the percentage and criteria for achievement of IPAS process skill ability indicators, it was discovered that there is one group of indicator achievement percentage of 20% with Very Good criteria, four groups of indicator achievement percentage of 80% with criteria (Good). Based on the results of data analysis, it can be concluded that the application of the project method students is enthusiastic in working on clippings and improving their elementary school science and science process skills for class V (centaurus) in the Merdeka curriculum.